Моделі та методи підвищення якості мобільного зв’язку шляхом застосування надширокосмугових технологій - Лазуренко, Богдан Олександрович (Національний технічний університет "Харківський політехнічний інститут", 2024)
Дисертаційна робота присвячена вирішенню актуальної науково-прикладної задачі, яка полягає у розробці методів забезпечення завадозахищеності із підтримкою якості обслуговування у безпроводових телекомунікаційних мережах на основі застосування надширокосмугових технологій. Метою дисертаційної роботи є розробка нових та удосконалення існуючих методів підвищення завадозахищеності телекомунікаційних мереж шляхом розробки і вдосконалення відповідних моделей і методів формування ансамблів складних сигналів. Об’єкт дослідження – процеси передачі інформації в безпроводових телекомунікаційних мережах. Предмет дослідження – моделі та методи забезпечення завадозахищеності із підтримкою якості обслуговування в безпроводових телекомунікаційних мережах. У вступі обґрунтовано актуальність забезпечення завадозахищеності на основі технології надширокосмугового зв’язку, представлено зв’язок роботи з науковими програмами, планами і темами, наведено наукову новизну, представлено практичне значення отриманих результатів, надано інформацію щодо особистого внеску здобувача, представлено перелік публікацій за темою дисертації. У першому розділі виконано постановку науково-технічної задачі забезпечення завадозахищеності у безпроводових телекомунікаційних мережах. Досліджено сучасний стан та тенденції подальшого розвитку методів організації систем мобільного зв’язку. Здійснено аналіз процесів передачі інформації та обґрунтовано доцільність застосування надширокосмугових сигналів в системах цифрового безпроводового мобільного зв’язку. Показано, що критерієм завадозахищеності є відношення середньої потужності інформаційного сигналу до потужності шуму. Доведено, що для забезпечення завадозахищеності при заданому рівні якості обслуговування, доцільно здійснити розробку та удосконалення нових моделей і методів на ґрунті технології надширокосмугових сигналів. Виконана формальна постановка задачі та сформульовані завдання дисертаційного дослідження. У другому розділі розроблено метод формування ансамблів складних сигналів в системах мобільного зв’язку. Запропоновано метод створення сигнально-кодової конструкції інформаційного сигналу та метод формування незалежних завадозахищених каналів зв’язку. Розроблено метод формування ансамблю складного надширокосмугового інформаційного сигналу та модель, яка реалізує розроблений метод одночасного формування опорного та інформаційного сигналів. Запропонований метод на основі складного надширокосмугового інформаційного сигналу дозволяє гарантовано забезпечити вимоги щодо завадозахищеності, прихованості і безпеки каналів безпроводового мобільного зв’язку. Розроблений метод формування складних інформаційних надширокосмугових імпульсних сигналів дозволяє збільшити щільність інформаційних каналів та обсяги інформації, що циркулює у безпроводових мережах із одночасним підвищенням її захищеності в умовах дії природних та штучних завад. У третьому розділі досліджено моделі і методи побудови антенних систем для реалізації технології надширокосмугового зв’язку. Розроблено метод випромінювання ансамблю складних надширокосмугових сигналів та модель антенної системи, що його реалізує. Причому формування біполярного імпульсного інформаційного сигналу, який являє собою еквівалент похідної моноциклу Гауса, здійснюють шляхом інтерференції його складових у еквівалентному загальному розкриві антени, що дозволяє у 2,37 разів підвищити радіус дії випромінювання антени. Створено і досліджено модель турнікетної антенної системи та метод мерехтливої поляризації, згідно якого кожен із серії чипів, що кодують інформаційний біт, по черзі подають на одну чи іншу антену, які в антенному блоці розташовані ортогональне, що дозволяє більш ніж удвічі підвищити радіус дії електромагнітного випромінювання антени Це також забезпечує прийом і передачу електромагнітного випромінювання довільної поляризації, яке характерне для безпроводових телекомунікаційних систем мобільного зв’язку. У четвертому розділі досліджено метод кореляційного прийому ансамблю складного сигналу, який дозволяє розпізнати і вилучити інформаційний сигнал із суміші гаусового білого шуму та корисного сигналу. Показано, що достовірне відновлення переданої бінарної інформації дозволяє за умови великої бази сигналу (B ˃ 300) здійснювати приховану передачу сигналу (с/ш = - 3 … - 6 дБ) із імовірністю похибки на біт менше, ніж 10-6. Проведено оцінку ефективності розроблених науково-технічних рекомендацій щодо їх практичного використання, що дозволяє здійснювати завадозахищену надійну передачу двійкової цифрової інформації в умовах виникнення зовнішніх та внутрішньосистемних завад. У висновках наведено основні результати наукової роботи щодо вирішення поставлених наукових задач дослідження. За результатами дослідження отримано такі наукові резульатти: 1.Вперше запропоновано метод формування ансамблю складного надширокосмугового інформаційного сигналу в системах мобільного зв’язку, який дає можливість здійснювати безпроводовий зв’язок в широкій смузі частот, коли рівень інформаційного сигналу дорівнює чи нижче рівня шуму. 2. Вперше запропоновано моделі і методи побудови антенних систем для реалізації технології надширокосмугового зв’язку та метод мерехтливої поляризації для телекомунікаційних систем безпровідного мобільного зв’язку, який враховує особливості створення, розповсюдження у просторі та прийому надширокосмугових інформаційних сигналів, що дозволяє виконати вимоги щодо забезпечення завадозахищеності безпроводових рухомих телекомунікаційних систем із підтримкою якості обслуговування. 3. Удосконалено метод одночасного кодування та модуляції інформації шляхом створення сигнально - кодової конструкції, який базується на зсуві у часі кодуючого сигналу щодо його основного положення у послідовності сигналів та відрізняється від відомих тим, що величина часового зсуву складає чверть тривалості кодуючого сигналу. 4. Удосконалено метод формування незалежних завадозахищених каналів із застосуванням ортогонального кодування, який базується на додатковому зсуві у часі кодуючого сигналу відносно опорної їх послідовності та відрізняється тим, що величина часового зсуву відносно опорної послідовності складає 2-3 порядки тривалості кодуючого сигналу, що дозволяє ущільнити канали зв’язку без порушення якості їх роботи. 5. Отримав подальший розвиток метод кореляційного прийому надширокосмугових сигналів, який дає можливість здійснювати подвійну спектральну обробку за час появи кожного біту інформації, що дозволяє збільшити співвідношення сигнал/завада на вході приймача. 6. Отримав подальший розвиток метод розпізнавання і вилучення інформаційного сигналу із суміші гаусового білого шуму та корисного сигналу шляхом кореляції прийнятого і опорного сигналу, що дозволяє підвищити достовірність прийому. Дослідження, результати яких викладені в дисертаційній роботі, виконані на кафедрі «Системи інформації ім. В.О. Кравця» НТУ «Харківський політехнічний інститут» відповідно до завдань держбюджетної теми МОН України: Міжнародний проект за програмою ERASMUS+ (Project Number: 598236-EPP-1-2018-1-LT-EPPKA2-CBHE-SP) за темою «dComFra – Digital competence framework for Ukrainian teachers and other citizens», в яких здобувач був виконавцем окремих етапів. За результатами дослідження підтверджено практичну та теоретичну цінність розроблених моделей та методів, надано практичні рекомендації, щодо застосування розроблених моделей та методів та розглянуто перспективи їх подальшого розвитку. The dissertation work is devoted to solving an urgent scientific and applied problem, which is to develop methods for ensuring interference immunity with maintaining the quality of service in wireless telecommunication networks based on the use of ultra-wideband technologies. The purpose of the dissertation work is to develop new and improve existing methods for increasing the noise immunity of telecommunication networks by developing and improving appropriate models and methods for forming ensembles of complex signals. Object of the research is the processes of information transmission in wireless telecommunication networks. The subject of research is is models and methods for providing noise immunity with quality of service support in wireless telecommunication networks. The introduction substantiates the relevance of providing noise immunity based on ultra-wideband communication technology, presents the connection of the work with scientific programs, plans and topics, provides scientific novelty, presents the practical significance of the results obtained, provides information on the personal contribution of the applicant, and presents a list of publications on the topic of the dissertation. In the first chapter, the scientific and technical problem of ensuring interference immunity in wireless telecommunication networks is formulated. The current state and trends in the further development of methods for organizing mobile communication systems are investigated. An analysis of information transmission processes is carried out and the feasibility of using ultra-wideband signals in digital wireless mobile communication systems is substantiated. It is shown that the criterion of noise immunity is the ratio of the average power of the information signal to the noise power. It is proved that in order to ensure noise immunity at a given level of service quality, it is advisable to develop and improve new models and methods based on ultra-wideband signal technology. The formal statement of the problem and the tasks of the dissertation research are formulated. In the second chapter, a method for forming ensembles of complex signals in mobile communication systems is developed. A method for creating a signal-code design of an information signal and a method for forming independent noise-protected communication channels are proposed. A method for forming an ensemble of complex ultra-wideband information signals and a model that implements the developed method of simultaneous formation of reference and information signals are developed. The proposed method, based on a complex ultra-wideband information signal, allows to guarantee the requirements for noise immunity, secrecy and security of wireless mobile communication channels. The developed method of forming complex ultra-wideband information pulse signals allows increasing the density of information channels and the amount of information circulating in wireless networks while improving its security under the influence of natural and artificial interference. In the third chapter, we study models and methods for constructing antenna systems for the implementation of ultra-wideband communication technology. A method for radiating an ensemble of complex ultra-wideband signals and a model of the antenna system that implements it have been developed. Moreover, the formation of a bipolar pulse information signal, which is the equivalent of the derivative of the Gaussian monocycle, is carried out by interfering its components in the equivalent total antenna opening, which allows to increase the radiation range of the antenna by 2.37 times. A model of a turnstile antenna system and a method of flickering polarization are created and studied, according to which each of a series of chips encoding an information bit is fed to a single antenna. They are alternately fed to one or the other antenna, which are arranged orthogonally in the antenna unit, which allows more than doubling the range of the antenna's electromagnetic radiation It also provides reception and transmission of electromagnetic radiation of arbitrary polarization, which is typical for wireless telecommunication systems of mobile communication. In the fourth chapter, we investigate the method of correlation reception of a complex signal ensemble, which allows us to recognize and extract an information signal from a mixture of Gaussian white noise and a useful signal. It is shown that the reliable recovery of the transmitted binary information allows, provided a large signal base (B ˃ 300) covert signal transmission (S/N = - 6... - 3 dB) with a bit error probability of less than 10-6. The effectiveness of the developed scientific and technical recommendations for their practical use has been evaluated, which allows for the reliable transmission of binary digital information in the face of external and intra-system interference. The conclusions present the main results of the scientific work on solving the research tasks. The research has yielded the following scientific results: 1. The method of forming an ensemble of a complex ultra-wideband information signal in mobile communication systems was first proposed, which makes it possible to carry out wireless communication in a wide frequency band when the level of the information signal is equal to or lower than the noise level. 2. For the first time, models and methods for constructing antenna systems for the implementation of ultra-wideband communication technology and the method of flickering polarization for telecommunication systems of wireless mobile communication, which takes into account the peculiarities of creating, distributing in space and receiving ultra-wideband information signals, which allows to fulfill the requirements for ensuring the noise immunity of wireless mobile TCS with maintaining the quality of service. 3. The method of simultaneous coding and modulation of information is improved by creating a signal-code construction based on the time shift of the coding signal relative to its basic position in the signal sequence and differs from the known ones in that the value of the time shift is a quarter of the duration of the coding signal. 4. An improved method of forming independent noise immune channels using orthogonal coding, which is based on an additional time shift of the coding signal relative to their reference sequence and is characterized by the fact that the value of the time shift relative to the reference sequence is 2-3 orders of magnitude of the duration of the coding signal, which allows to compact communication channels without compromising the quality of their operation. 5. The method of correlation reception of ultra-wideband signals was further developed, which makes it possible to perform double spectral processing during the appearance of each bit of information, which allows to increase the signal-to-noise ratio at the receiver input. 6. The method of recognizing and extracting an information signal from a mixture of Gaussian white noise and a useful signal by correlating the received and reference signals was further developed, which allows to increase the reliability of reception. The research, the results of which are presented in the dissertation, was carried out at the department "Information Systems named after V.O. Kravets" of NTU "Kharkiv Polytechnic Institute" in accordance with the tasks of the state budget topic of the Ministry of Education and Culture of Ukraine: International project under the ERASMUS+ program (Project Number: 598236-EPP-1-2018-1-LT-EPPKA2-CBHE-SP) on the topic "dComFra – Digital competence framework for Ukrainian teachers and other citizens" (implementation period 2018-2021), in which the applicant was the executor of individual stages. Based on the results of the study, the practical and theoretical value of the developed models and methods was confirmed, practical recommendations were given regarding the application of the developed models and methods, and the prospects for their further development were considered.
Models and Methods for Improving the Quality of Mobile Communication by Using Ultra-Wideband Technologies
Keywords: аналіз; відмовостійкість; випромінювання; електромагнітна сумісність; завадостійкість; кодування; кореляція; методи; мережа; модель; моделювання; якість обслуговування; сигнал; analysis; fault tolerance; radiation; electromagnetic compatibility; interference immunity; coding; correlation; methods; network; model; quality of service; signal